Механические свойства стеклопластика, модифицированного наноалмазами и углеродными нанотрубками, в интервале температур 77–373 К - Лотоцкая, В.А.; Яковенко, Л.Ф.; Алексенко, Е.Н.; Желтов, П.Н.; Малый, Н.А.; Гавриленко, А.М.; Богатырева, Г.П. (Вісник Українського матеріалознавчого товариства, 2013)
The influence of temperature on a rupture stress and the module of elasticity of the combined fibreglasses based on continuous reinforcing fiberglass fabric in combination with epoxy binder in volume of which are distributed nanodimensional particles (carbon nanotubes or nanodimensional particles of diamond) is investigated. It is shown, that concentration dependences of mechanical characteristics of the fibreglasses modified nanoparticles, and have nonmonotonic character. The maximal increase of examined characteristics of the modified composites does not exceed 12 % from reference values. At temperature downturn the values of both characteristics are increased, and their concentration dependences are displaced aside smaller values concerning of initial fiberglass.